Value of imaging examinations in diagnosing lumbar disc herniation: A systematic review and meta-analysis - Huang, Zhihao; Zhao, Pengfei; Zhang, Chengming; Wu, Jingtao; Liu, Ruidong (Frontiers in Surgery, 2023)
Introduction: To systematically review the clinical value of three imaging examinations (MRI, CT, and myelography) in the diagnosis of LDH. Methods and analysis: Databases including PubMed, Embase, The Cochrane Library, Web of Science, CBM, CNKI, WanFang Data, and VIP were electronically searched to collect relevant studies on three imaging examinations in the diagnosis of LDH from inception to July 1, 2021. Two reviewers using the QUADAS-2 tool independently screened the literature, extracted the data, and assessed the risk of bias in included studies. Then, meta-analysis was performed by using Meta-DiSc 1.4 software and Stata 15.0 software. Results: A total of 38 studies from 19 articles were included, involving 1,875 patients. The results showed that the pooled Sen, pooled Spe, pooled +LR, pooled −LR, pooled DOR, AUC of SROC, and Q* were 0.89 (95%CI: 0.87–0.91), 0.83 (95%CI: 0.78–0.87), 4.57 (95%CI: 2.95–7.08), 0.14 (95%CI: 0.09–0.22), 39.80 (95%CI: 18.35–86.32), 0.934, and 0.870, respectively, for MRI. The pooled Sen, pooled Spe, pooled +LR, pooled −LR, pooled DOR, AUC of SROC, and Q* were 0.82 (95%CI: 0.79–0.85), 0.78 (95%CI: 0.73–0.82), 3.54 (95%CI: 2.86–4.39), 0.19 (95%CI: 0.12–0.30), 20.47 (95%CI: 10.31–40.65), 0.835, and 0.792, respectively, for CT. The pooled Sen, pooled Spe, pooled +LR, pooled −LR, pooled DOR, AUC of SROC, and Q* were 0.79 (95%CI: 0.75–0.82), 0.75 (95%CI: 0.70–0.80), 2.94 (95%CI: 2.43–3.56), 0.29 (95%CI: 0.21–0.42), 9.59 (95%CI: 7.05–13.04), 0.834, and 0.767 respectively, for myelography. Conclusion: Three imaging examinations have high diagnostic value. In addition, compared with myelography, MRI has a higher diagnostic value.